Laser-clad Al-Ti-Zr and Cr-Ti-Zr coatings on Zr alloy: composition-induced microstructural and hardness differences. (December 2022) - Wang, Yueyuan; Chai, Linjiang; Zhang, Fangli; Qi, Lan; Luo, Jinru; Wang, Hui; Li, Yuqiong; An, Xuguang
Abstract: In this study, Al-Ti-Zr and Cr-Ti-Zr metallic coatings with thichness of 250-280 μm were fabricated successfully on Zr alloy using pulsed laser cladding. By jointly employing multiple characterization techniques, microstructural characteristics of the coatings were probed with their formation reasons explored. The Al-Ti-Zr coating consists of a single BCC solid-solution phase (average size 8.6 ± 6.3 μm) with hardness of 405.5 ± 16.6 HV that is more than twice that of the substrate (198.7 ± 2.0 HV). Such marked hardening is mainly related to the contribution from the solid-solution strengthening produced by Al and Ti. The Cr-Ti-Zr coating consists of cellular BCC phase (average size 0.9 ± 0.4 μm) and C14-type Cr2 (Ti, Zr) Laves phase with nanoscale lamellar structures. Its average hardness is 584.8 ± 33.6 HV, about three times of that of the substrate, which can be ascribed to synergistic effects of solid-solution, grain refinement and second phase strengthening. The formation of the single BCC solid-solution phase in the Al-Ti-Zr coating is mainly due to the relatively small differences in atomic size and electronegativity between Al, Ti and Zr. For the Cr-Ti-Zr coating, however, due to large atomic size and electronegativity differences between Cr and Zr (as well as Cr and Ti), Cr2 (Ti, Zr) Laves phase was formed in addition to the BCC phase. Graphical abstract: Unlabelled Image Highlights: Al-Ti-Zr and Cr-Ti-Zr metallic coatings were fabricated successfully on a Zr alloy using pulsed laser cladding. Al-Ti-Zr coating consists of a single BCC solid-solution phase due to relatively small δ and Δ x between Al, Ti and Zr. In Cr-Ti-Zr coating, large δ and Δ x between Cr and Zr/Ti result in Cr2 (Ti, Zr) Laves phase with refined BCC phase. Average hardnesses of Al-Ti-Zr and Cr-Ti-Zr coatings are 405.5 ± 16.6 HV and 584.8 ± 33.6 HV, markedly higher than the substrate. Solid-solution, grain refinement and second phase strengthening jointly lead to high hardness of Cr-Ti-Zr coating.